The plantation in the postslavery imagination - Russ, Elizabeth Christine (New York ; Oxford : Oxford University Press, 2010)
The author examines the persistent presence of the plantation in trans-American literatures of the last century. She conceives the plantation to be not primarily a physical location, but rather an ideological and psychological trope through which intersecting histories of the New World are told and retold.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Plantations in literature; Spanish American fiction -- 20th century -- History and criticism; Caribbean fiction (Spanish) -- 20th century -- History and criticism; American literature -- 20th century -- History and criticism